(3QbGHI JSjjQ GdeDSSI aj Xd GbJUGO GdShb (B/s - (3UGdM, NGdU UGajs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2007)
(3eONd Edi QbGHI GdJSjjQ aj Xd GbJUGO GdShb,GdQbGHI Ydi eGdjI GdeDSSI,JHhjH GdJcGdja aj GdeDSSI,GSJYeGd GdJcGdja cCOGI ddQbGHI Ydi GdJSjjQ,fbWI JYGOd JMOjOgG hGSJYeGdgG cCOGI QbGHjI,GdJcGdja GdeYjGQjI,GdejRGfjI GdJbOjQjI cCOGI QbGHjI,QbGHI GdJSjjQ fXGe ddeYdheGJ hGJNGP GdbQGQGJs
(3HHdjhZQGajG(B:(3U U(B.289-292s
Keywords: (3GdEbJUGOs